Large Room‐Temperature Electroresistance in Dual‐Modulated Ferroelectric Tunnel Barriers. (16th March 2015) - Radaelli, Greta; Gutiérrez, Diego; Sánchez, Florencio; Bertacco, Riccardo; Stengel, Massimiliano; Fontcuberta, Josep
<x xml:space="preserve">Abstract</x> Pt/BaTiO3/La0.7Sr0.3MnO3 tunnel junctions, at negative voltage bias, for two polarization directions are represented. It is demonstrated that reversing the polarization direction of a ferroelectric barrier in a tunnel junction leads to a change of junction conductance and capacitance, with concomitant variations on the barrier height and effective thickness, both contributing to produce larger electroresistance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>